The effect of finger painting on socio-emotional development of preschool children aged 5-6 years - Raniana Aknes Pertiwi; Santi Oktavia; Yuli Lestari (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Social-emotional development is an important aspect of early childhood development because it helps children interact and adapt to their environment. Appropriate stimulation is needed to support optimal social-emotional development in preschool children. One form of stimulation that can be given is finger painting activities which can encourage creativity, emotional expression, and social interaction among children. Purpose: To determine the effect of finger painting on the socio-emotional development of preschool children aged 5–6 years. Method: This study used a quantitative method with a pre-experimental design using a one-group pretest-posttest approach. The population in this study were children aged 5–6 years at PAUD Al Barokah Labuhan Ratu, East Lampung. The sample consisted of 20 children using a total sampling technique. The instrument used was a social-emotional development observation sheet adapted from the child development achievement standards based on Permendikbud No. 137 of 2014. Data analysis was carried out using univariate and bivariate analysis with the Wilcoxon test at a significance level of 95% (α = 0.05). Results: The results showed that the average score of children's socio-emotional development before the intervention was 2.20 and increased to 3.80 after the finger-painting intervention, with a mean difference of 1.60. The statistical test results obtained a p-value of 0.000 (<0.05), indicating that there was a significant effect of finger painting on the socio-emotional development of preschool children aged 5–6 years. Conclusion: Finger painting has a significant effect on improving the socio-emotional development of preschool children aged 5-6 years. Suggestion: Parents and teachers are encouraged to provide creative stimulation activities such as finger painting regularly to support children's socio-emotional development.